SISTEM MONITORING KEBAKARAN BERBASIS SMS GATEWAY - Joniwarta Joniwarta; Allan D Alexander; Dwi Budi Srisulistiowati (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2019)
Fire disasters that are not immediately dealt with can certainly cause losses both property losses and loss of life. This happens because some are good from short circuiting, throwing cigarette butts at random, exploding and burning objects and delaying information obtained by firefighters or school officials SMK Mandalahayu Bekasi during incidents of fire disasters. In this study a fire source fire Monitoring System Was Built Based On SMS Gateway At using MQ-135 as a smoke sensor which functions to detect smoke from fire, DS18B20 as a temperature sensor that functions to detect the temperature in the surrounding room, Buzzer alarm as a sound warning and SIM Module GSM900A as an SMS sending media, which is used to provide information about the detection of fire sources as early as possible, so that fire disasters are handled as soon as possible and the risk of fire can be minimized and routinely dominate the room using a camera Keywords: Fire,Â  Buzzer, SMS gateway